Ethnoscience-Based Learning Supported by Learning Management Systems (LMS) to Enhance Students’ Digital Literacy and Collaborative Skills - Herayanti, Lovy; Fuaddunnazmi, Fuaddunnazmi; Safitri, Baiq Rina Amalia (Department of Physics Education, Universitas Mataram, 2025)
21st-century learning demands the development of digital literacy and collaboration skills as key competencies for students to adapt to the era of digital transformation and global society. This research aims to comprehensively examine the application of ethnoscience learning assisted by Learning Management System (LMS) in the context of higher education to enhance both skills. Ethnoscience, which integrates local knowledge and cultural wisdom with modern scientific concepts, offers a contextual and meaningful learning approach. Meanwhile, LMS provides a flexible and interactive online learning environment, supporting access to materials, discussions, and collaborative activities anywhere and anytime. The research method used is a systematic literature review (SLR), systematically identifying, evaluating, and synthesizing findings from various relevant studies published between 2020-2025. The main research question focuses on how the integration of ethnoscience and LMS can support the improvement of students' digital literacy and collaboration skills in science learning in higher education. The literature synthesis results show that ethnoscience learning assisted by LMS has significant potential in improving students' digital literacy through projects creating digital content based on culture, such as documentary videos or scientific blogs. Additionally, LMS facilitates collaboration skills by providing features such as discussion forums, online group assignments, and project management that enable cross-cultural interaction and meaning negotiation. Various good practices have been identified, such as the development of digital ethnoscience modules and the application of PjBL learning models integrated with LMS. However, challenges such as limited lecturer competence in LMS and ethnoscience, uneven technological infrastructure, and students' digital literacy gaps still need to be addressed. As a recommendation, ongoing training programs are needed for lecturers and students to improve digital competence and contextual pedagogy. Content developers and LMS managers must collaborate with cultural experts to design relevant and inclusive materials. Further research based on real classes is essential to evaluate the effectiveness of this model empirically and sustainably. This model can be a solution in preparing students to face the complexities of learning and the 21st-century workforce.